TRAUMA HEALING BERBASIS ISLAMI MELALUI KEGIATAN EDUKATIF NONFORMAL PADA ANAK PASCABENCANA BANJIR BANDANG DI KELURAHAN GURUN LAWEH KOTA PADANG - Deti Yulia Martiana; Alimun Pajri; Nur Hidayah; Yoga Adiansah Nasir; Muhammad Kosim; Wilrahmi Izzati (Jurnal Manajemen Pendidikan, 2026)
This study aims to comprehensively analyze the form and implementation of Islamic-based trauma healing activities through nonformal education, examine the strategy of inculcating religious attitudes in children, as well as evaluate its impact on the psychosocial recovery of children post-flood disaster in Gurun Laweh Village, Padang City. This study used a qualitative approach with a case study design. Data were obtained through in-depth interviews of children of activity participants, volunteers, speakers, community leaders (RT Leaders), and parents, participatory observation during the implementation of trauma healing activities, as well as a study of program documentation. The results of the study showed that Islamic-based trauma healing activities were implemented through nonformal educational activities such as joint prayer, Qur’anic verse reading and interpretation, prophetic exemplary stories, Islamic-tinged educational games, as well as empathy-based emotional companionship. The strategy of cultivating a religious attitude is carried out through spiritual habituation, the example of volunteers, and the internalization of the value of patience, trust, as well as optimism in the face of adversity. The activity had a positive impact on the psychosocial recovery of the child, which was indicated by the increased emotional calmness, sense of security, as well as the child’s courage in social interaction. This study contributes to enriching the study of Islamic values-based trauma healing in the context of postdisaster nonformal education.